Fundamentals of nursing : the art and science of nursing care - Taylor, Carol [ (Carol R.)] (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Fundamentals of Nursing: The Art and Science of Nursing Care, Seventh Edition, promotes nursing as an evolving art and science, directed to human health and well-being. It challenges students to cultivate the blended skills they will need to serve patients and the public well. Our aim is to prepare nurses who combine the highest level of scientific knowledge and technologic skill with responsible, caring practice. We want to challenge students to identify and master the cognitive and technical skills as well as the interpersonal and ethical/ legal skills they will need to effectively nurse the patients in their care"--Provided by publisher